Laparoscopic Nissen fundoplication. - Jamieson, G G (1994)
OBJECTIVE: The authors laparoscopic approach for a Nissen fundoplication is presented. SUMMARY BACKGROUND DATA: The technique has been undertaken in 155 patients over 29 months, with 137 patients having been observed for more than 3 months. METHODS: Three hundred sixty degree fundoplication was undertaken using three or four sutures to secure the wrap. Short gastric vessels were not divided, and the anterior wall of the stomach was used to construct the wrap around the esophagus with a large bougie in position. RESULTS: The operation was not completed laparoscopically in 19 patients because a satisfactory wrap could not be achieved. Ten patients undergoing laparoscopic fundoplication underwent a subsequent operation related to the laparoscopic procedure within 6 months, and there was one postoperative death. Seven other patients were readmitted to the hospital several days subsequent to their discharge, four because of pulmonary emboli. Of 137 patients who have been observed for more than 3 months, 133 patients are well and currently are free from reflux symptoms. CONCLUSIONS: In uncomplicated cases, laparoscopic fundoplication has similar advantages to laparoscopic cholecystectomy. In spite of the fact that it has not yet achieved the overall usefulness of open fundoplication, it seems likely that laparoscopic fundoplication will be used increasingly in the treatment of patients with gastroesophageal reflux disease.